A fundamentação da igualdade liberal em Ronald Dworkin. - Bittencourt, Patrícia Xavier (2014)
The aim of this work is to analyze the Liberal Equality proposed by Ronald Dworkin. The philosopher presents a coherent version that intends to include the values of liberty, equality, justice and community, without the occurrence of conflicts among them. In this Equalitarian Liberalism, the principles of ethic individualism are highlighted: the equal value and the special responsibility. To achieve this goal, Dworkin chooses for the equality of resources, over the equality of welfare, in order to distribute the resources in the most egalitarian way, through an auction, in which people will make conscious choices and will make bids to the acquisition of available goods, in a way that no person wants the share of resources of another. The enforcement of the theory generates political consequences, mainly imposing obligations to the Government, such as to treat their citizens with equal consideration and respect, in a genuine way.